An Act To Control The Possession, Sale, Transfer And Use Of Pistols And Other Dangerous Weapons In The District Of Columbia, To Provide Penalties, To Prescribe Rules Of Evidence, And For Other Purposes, 47 Stat. 650 (1932) - (:unkn) unknown (My University, 1932)
Ch. 465, §§ 1, 8: Prohibited being armed with or having readily available any pistol or other firearm while committing a violent crime. In addition to being punished for the crime, will also be punished with imprisonment (various terms depending on the number of previous convictions). Additionally, Prohibited people convicted of violent crimes from owning or possessing a pistol. Prohibited carrying a concealed deadly or dangerous weapon. Regulates the sale and transfer of pistols.
Keywords: CARRY - CONCEALED; CARRY - INTENT TO COMMIT CRIME; POSSESSION - DANGEROUS PERSONS